(untitled) (Research, Society and Development, 2021)
Problem-based learning (PBL) is a student-centered instructional (and curricular) method, empowering learners to conduct research, integrating theory into practice and applying knowledge and skills to develop a viable solution to the defined problem. This article deals with a descriptive, exploratory study with a quantitative approach, carried out through an online questionnaire with 34 students of the higher course of Aesthetics and Cosmetics. The data were analyzed through simple descriptive analysis and presented in graphs. The study concluded, through the students’ perception, that the PBL method provides the development of clinical reasoning and self-directed study skills, which are essential capacities for professional performance.